Управління професійно-технічною освітою на державному та регіональному рівнях: зарубіжний досвід - Грень, Лариса Миколаївна (Університет митної справи та фінансів, 2019)
На підставі досвіду економічно розвинених країн (Сполучених Штатів Америки (США), Німеччини, Франції, Канади) з’ясовано, що є пряма залежність темпів удосконалення та розвитку виробництва від рівня професійної підготовки кадрів; розглянуто відповідальність урядів окремих штатів США за стан справ у галузі професійної освіти, при управліннях яких функціонують Бюро директора з питань професійної освіти, Ради професійного навчання, а на федеральному рівні – Бюро професійної освіти й освіти дорослих з підпорядкованим йому Національним науково-дослідним центром професійного навчання і Національна консультативна рада з фахової освіти. Розглянуто систему навчання у Німеччині, де підготовка кваліфікованих робітників здійснюється за дуальною формою навчання; з’ясовано, що держава контролює навчання у професійній школі, а торгово-промислова і реміснича палати здійснюють контроль навчання на виробництві; доведено, що на підставі Закону про професійну освіту регламентуються права й обов’язки підприємця і того, хто навчається. Доведено сувору централізацію системи освіти Франції, де підготовка кадрів у державних і приватних ліцеях перебуває під контролем держави; з’ясовано, що єдина стратегія в галузі професійного навчання розробляється міністерством професійної освіти, а відповідальність за фінансування професійних ліцеїв несе держава. З’ясовано, що у межах проєкту "Децентралізація управління професійним навчанням в Україні" було вивчено досвід канадської системи професійної освіти, яка, на відміну від української, є децентралізованою; доведено, що в Канаді в кожній провінції діє власна система професійної підготовки, проте управління ПТНЗ здійснюється за допомогою громадських формувань і у кожному закладі працює рада директорів (представників територіальної громади), яка здійснює стратегічне управління і до компетенції якої належить призначення і звільнення керівництва закладу професійної освіти. Обґрунтовано доцільність впровадження найкращого досвіду розвинених країн щодо управління вітчизняною професійно-технічною освітою на державному та регіональному рівнях, а саме: – реалізацію дуальної форми навчання у професійно-технічних навчальних закладах; – запровадження прямих фінансових стимулів для підприємств, які організують професійну підготовку, у формі надання пільг, відшкодування витрат на неї або грантів; – упровадження механізмів посилення соціально-економічного захисту працівників та учнів професійно-технічної освіти.

Based on the experience of economically developed countries (the United States of America (USA), Germany, France, Canada), it has been found that there is a direct dependency of improvement and production development rates on the level of personnel’s professional training. It was shown that in the USA, responsibility for vocational training issues is borne by the governments of the individual states whose educational directorates operate the Office of the Director of Vocational Education. It was also found, that in each state, there are Vocational Training Boards, and at the federal level there is the Bureau of Vocational and Adult Education with its National Vocational Training Research Center and the National Advisory Board on Vocational Education; the structure of the US vocational education system is presented. There was analyzed the training system in Germany, where the training of skilled workers is carried out at the enterprises in the apprenticeship system by the dual form of training; it was found that the state controls training in vocational schools, and the Chamber of Commerce and Industry controls the training in production. It is proved that on the basis of the Law on Vocational Training the rights and obligations of the entrepreneur and the student are regulated, that the entrepreneurs are personally selected by students in the educational centers, and the training is carried out on the basis of the contract on industrial apprenticeship. The Federal Institute for Vocational Education in Germany develops and approves, with the relevant branch ministry, instructions governing the content and process of teaching a particular profession. The rigorous centralization of the education system of France has been proved, where personnel training at public and private lyceums is under state control. It was found that a unified vocational education strategy is developed by the Ministry of Vocational Education and that the state that holds the diploma monopoly is responsible for financing vocational lyceums. Vocational education has been found to be free of charge and secular, and laws, ordinances and other educational documents are adopted at the state level and are binding on everyone. It was found that the experience of the Canadian vocational training system, which, unlike the Ukrainian one, is decentralized, was explored within the framework of the Decentralization of Vocational Training Management in Ukraine project. It is proved that in each province there is a system of vocational training, however the management of a vocation-and-technical training institution (VTTE) is carried out with the help of public formations, and in each institution there is a board of directors (representatives of the territorial community), which carries out strategic management and the competence of which includes appointment and dismissal of a VTTE’s management. Vocational training institutions in Canada have a leading role in training skilled workers for local and regional job markets. An important difference in the management of VTTEs is considered: the selection of teaching staff is made by certain criteria, namely: appropriate qualification level (determined by the industry professional association), considerable practical experience in the specialty, teachers’ pedagogical training and pedagogical experience. The expediency of introducing the best experience of the developed countries on the management of national vocational education at the national and regional levels is substantiated, namely: – realization of the dual form of training in vocational schools, which solves the actual tasks of adapting professional knowledge, skills, graduates’ ability of adapting to rapidly changing conditions of the labor market; practical training improvement; training of specialists who meet employers’ qualification requirements and professional standards; confirmation of the competitiveness of a skilled worker in the labor market; – the introduction of direct financial incentives for enterprises providing vocational training in the form of benefits, reimbursement or grants; – introduction of mechanisms for strengthening socio-economic protection of workers and students of vocational education.
Management of professional and technical education at the state and regional levels: foreign experience
Keywords: державне управління; децентралізація; вища освіта; навчальний процес; економіка; освітні послуги; public administration; vocational education; regional level; decentralization; foreign experience